Controlled Sink Mobility Algorithms for Wireless Sensor Networks - Metin Koç; Ibrahim Korpeoglu (International Journal of Distributed Sensor Networks)
A wireless sensor network (WSN) consists of hundreds or thousands of sensor nodes organized in an ad hoc manner to achieve a predefined goal. Although WSNs have limitations in terms of memory and processors, the main constraint that makes WSNs different from traditional networks is the battery problem which limits the lifetime of a network. Different approaches are proposed in the literature for improving the network lifetime, including data aggregation, energy efficient routing schemes, and MAC protocols. Sink node mobility is also an effective approach for improving the network lifetime. In this paper, we investigate controlled sink node mobility and present a set of algorithms for deciding where and when to move a sink node to improve network lifetime. Moreover, we give a load-balanced topology construction algorithm as another component of our solution. We did extensive simulation experiments to evaluate the performance of the components of our mobility scheme and to compare our solution with static case and random movement strategy. The results show that our algorithms are effective in improving network lifetime and provide significantly better lifetime compared to static sink case and random movement strategy.